2023
DOI: 10.1007/s11356-023-27743-2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis, oxidative stress, hormonal, and histological alterations in the reproductive system of thiamethoxam-exposed female rats

Abstract: The present study aimed to investigate the oral toxic effects of 1/10 LD50 and 1/5 LD50 of thiamethoxam (TMX), a neonicotinoid insecticide, on the reproductive system of female Wistar rats. Thirty female rats were divided into three groups and supplied orally with either; saline solution, 1/10 LD50 of TMX (156 mg/kg) or 1/5 LD50 of TMX (312 mg/kg). The daily administration was extended for 30 days. Investigating the parameters of oxidative stress, hormonal levels, histopathological alterations, and the apoptot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…It was reported that thiamethoxam, one of the neonicotinoids, induced pathological lesions in the uterus and ovaries of rats and increased caspase-3 immunoreactivity in the uterus and ovaries compared to the control group. Furthermore, it was reported that Bcl-2 levels, one of the markers associated with apoptosis, were down-regulated, the Bax/bcl-2 ratio rose by up to 52% in contrast to the control group, and p53 expression was up-regulated (El-Din et al, 2023). A study by Nur et al in which they examined the immunoreactivity of Bcl-2 and p53 apoptotic markers showed an increased expression of p53-one of the cell death receptors parallel with the pathological changes in the kidneys resulting from acetamiprid-induced nephrotoxicity and a decrease in antiapoptotic Bcl-2 expression due to suppression (Nur et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that thiamethoxam, one of the neonicotinoids, induced pathological lesions in the uterus and ovaries of rats and increased caspase-3 immunoreactivity in the uterus and ovaries compared to the control group. Furthermore, it was reported that Bcl-2 levels, one of the markers associated with apoptosis, were down-regulated, the Bax/bcl-2 ratio rose by up to 52% in contrast to the control group, and p53 expression was up-regulated (El-Din et al, 2023). A study by Nur et al in which they examined the immunoreactivity of Bcl-2 and p53 apoptotic markers showed an increased expression of p53-one of the cell death receptors parallel with the pathological changes in the kidneys resulting from acetamiprid-induced nephrotoxicity and a decrease in antiapoptotic Bcl-2 expression due to suppression (Nur et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…With growing evidence of NEO neurotoxicity, there is an urgent need for a better understanding of their negative effects on nontarget organisms (Wang et al 2018 ; Habotta et al 2023 ). TMX is a potent NEO insecticide that has been shown to affect a variety of physiological indices and histological structures in albino rats (El-Din et al 2023 ). LC has already been shown to have a significant neuroprotective effect against aspartame (Hamza et al 2020 ), atrazine (Aziz et al 2018 ), bisphenol A (Edres et al 2018 ), and valproic acid (Nouri et al 2022 ; Salimi et al 2022 ) toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the delicate balance within the ovarian cells is disrupted. The apoptosis process is initiated as a protective response to eliminate cells that are severely affected by the ROS-induced damage [ 75 , 76 , 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%